EXTH-46. RNA LIPID PARTICLES INDUCE BI-DIRECTIONAL IMMUNITY AGAINST DIFFUSE MIDLINE GLIOMA. (14th November 2022) - McGuiness, James; Weidert, Frances; Zhang, Dingpeng; Grippin, Adam; Karachi, Aida; Qdaisat, Sadeem; Thomas, Nagheme; Castillo, Paul; Huang, Jianping; Ligon, John; Silver, Natalie; Rahman, Maryam; et al.
Abstract: BACKGROUND: Diffuse Intrinsic Pontine Glioma (DIPG) is uniformly fatal. Upon diagnosis, DIPG cannot be safely debulked and systemic therapies have unproven benefit. Immunotherapy can overcome these obstacles, but objective responses are rare; and cancer antigens, even when tumor specific (i.e. H3K27M), are usually poorly immunogenic. OBJECTIVE: We sought to develop a murine model of diffuse midline glioma (DMG) that better recapitulates human disease. In these models, we tested different iterations of mRNA loaded nanoparticle (NP) vaccines for their therapeutic effect. APPROACH: We implanted murine gliomas (expressing H3K27M mutation) midline into developing neonatal brains. We manufactured different mRNA constructs encoding for foreign proteins (e.g. GFP), H3K27M or wildtype H3K27 and evaluated immunogenicity and anti-tumor efficacy. These mRNA vaccines were layered into lipid particles (RNA-NP) and administered intravenously when animals became acutely symptomatic (similar to when patients are diagnosed). RESULTS: Surprisingly, all mRNA constructs tested were sufficient to elicit anti-tumor efficacy against DMGs. This was true for both antigen specific (H3K27M) and non-antigen specific constructs (GFP, H3K27 wildtype). While H3K27M encoding RNA-NPs were superior to H3K27 wildtype encoding RNA-NPs (p=0.057), the adaptive immune effects appear marginal relative to the innate immune responses generated by all RNA-NP constructs. These innate responses are characterized by induction of type I interferon response from plasmacytoid DCs. Interestingly, these effects could not be recapitulated in murine models of adult type glioblastoma (KR158b) which required antigen specificity for induction of anti-tumor efficacy. CONCLUSION: These data suggest that pediatric gliomas may be particularly sensitive to innate immunity. We have optimized development of a target H3K27M mRNA construct that balances innate and adaptive bi-directional immune induction. We are completing FDA-IND enabling data to support translation of H3K27M loaded RNA-NPs into human clinical trials.